Enhanced Bioremediation Potential of Shewanella decolorationis RNA Polymerase Mutants and Evidence for Novel Azo Dye Biodegradation Pathways - Cai, Xunchao; Zheng, Xin; Wang, Yicheng; Tian, Li; Mao, Yanping (Frontiers in Microbiology, 2022)
Bioremediation has been considered as a promising method for recovering chemical polluted environments. Here Shewanella decolorationis strain Ni1-3 showed versatile abilities in bioremediation. To improve the bioremediation activity, RNA polymerase (RNAP) mutations of strain Ni1-3 were screened. Eleven mutants were obtained, of which mutant #40 showed enhanced amaranth (AMR) degradation capacity, while mutant #21 showed defected capacity in AMR degradation but greatly enhanced capacity in cathodic metal leaching with 3~4 times faster than the wild-type (WT) strain Ni1-3, suggesting that different pathways were involved in these two processes. Transcriptional profiling and gene co-expression networks between the mutants and the WT stain disclosed that non-CymA-Mtr but cytochrome b and flavin oxidoreductase dominated azo dye degradation pathway existed in S. decolorationis, which involved key proteins TorC, TorA, YceJ, YceI, Sye4, etc. Furthermore, the involvement of TorA was verified by trimethylamine N-oxide reduction and molybdenum enzyme inhibitory experiments. This study clearly demonstrates that RNAP mutations are effective to screen active microbial candidates in bioremediation. Meanwhile, by clarifying the novel gene co-expression network of extracellular electron transfer pathways, this study provides new insights in azo dye degradation and broadens the application of Shewanella spp. in bioremediation as well.